2022
DOI: 10.1038/s41556-022-00877-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR screen identifies PRC2 and KMT2D-COMPASS as regulators of distinct EMT trajectories that contribute differentially to metastasis

Abstract: Epithelial-mesenchymal transition (EMT) programs operate within carcinoma cells in which they generate phenotypes associated with malignant progression. In their various manifestations, EMT programs enable epithelial cells to enter into a series of intermediate states arrayed along the E-M phenotypic spectrum. At present, we lack a coherent understanding of how carcinoma cells control their entrance into and continued residence in these various states, and which of these states favor the process of metastasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 67 publications
7
83
0
Order By: Relevance
“…Long-term treatment with a Wnt agonist would direct the equilibrium towards the plastic-dormant state, without affecting the cell-state itself. This is supported by reports of similar phenotype transitions caused by long-term in vitro treatments or targeted genetic manipulation of signalling pathways 36,37 . However, such state-transitions were also reported to occur spontaneously and were found to be a pre-requisite for metastatic outgrowth 38 .…”
Section: Discussionsupporting
confidence: 65%
“…Long-term treatment with a Wnt agonist would direct the equilibrium towards the plastic-dormant state, without affecting the cell-state itself. This is supported by reports of similar phenotype transitions caused by long-term in vitro treatments or targeted genetic manipulation of signalling pathways 36,37 . However, such state-transitions were also reported to occur spontaneously and were found to be a pre-requisite for metastatic outgrowth 38 .…”
Section: Discussionsupporting
confidence: 65%
“…Yet it remains to be determined what exactly triggers its activation. BRCA1 itself has recently been identified as a guardian of the epithelial states (Zhang et al 2022) - inactivation of BRCA1 by CRISPR leads to increased EMP in mammary cells. Another trigger of EMT could also be senescence - itself induced by extensive genomic rearrangements following Trp53 and Brca1 deletion.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a spectrum of hybrid epithelial–mesenchymal (hybrid E/M) cells, such as quasi-epithelial cells and quasi-mesenchymal cells, express both epithelial and mesenchymal markers and show intermediate phenotypes. Single-cell analyses of EMT processes have revealed that hybrid E/M cells go through sequential and parallel trajectories caused by context-dependent EMT signaling, chromatin modulation and transcriptional effects [ 41 , 42 ]. SNAI1 (Snail), SNAI2 (Slug), TWIST1, ZEB1 (zinc finger E-box binding homeobox 1) and ZEB2 are key transcription factors that reprogram epithelial cells toward hybrid E/M cells and mesenchymal cells under the control of WNT, FGF, Hedgehog, Notch, TGFβ and other signaling cascades ( Figure 3 ).…”
Section: Epithelial–mesenchymal Plasticitymentioning
confidence: 99%